Pengaruh Konten Instagram Wensen School Indonesia Terhadap Brand Image - Amelia, Andini; alfirahmi, alfirahmi (LUGAS Jurnal Komunikasi, 2024)
The Influence of Wensen School Indonesia's Instagram Content on Brand Image Andini Amelia CG191120543 The phenomenon of branding in Indonesia at this time has begun to shift, because the intended target consumer comes more from social media. The use of social media to improve brand image is considered appropriate through interaction with the audience on the content it creates. Many schools in Indonesia have used Instagram social media to create a brand image, one of which is a school called Wensen School Indonesia. Instagram is used by Wensen School Indonesia to upload photos and videos of various activities, and programs that are being run, as well as create interesting content to build a good view for followers. Therefore, the purpose of this study is to determine and analyze how much influence Instagram content has on the brand image of Wensen School Indonesia. This type of research uses quantitative descriptive method of distributing questionnaires online to Instagram followers @wensenschoolindonesia. The results of this study showed that with a sample of 100 followers, the output value of the coefficient of determination (R Square) is 0.588 or 59.3%. This shows that wensen School Indonesia's Instagram content has an influence on brand image of 59.3% while 40.7% are influenced by other factors.